2019
DOI: 10.1093/hmg/ddz063
|View full text |Cite
|
Sign up to set email alerts
|

Rare variants in MYH15 modify amyotrophic lateral sclerosis risk

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurological disorder characterized by progressive muscular atrophy and respiratory failure. The G4C2 repeat expansion in the C9orf72 gene is the most prevalent genetic risk for ALS. Mutation carriers (C9ALS) display variability in phenotypes such as age-at-onset and duration, suggesting the existence of additional genetic factors. Here we introduce a three-step gene discovery strategy to identify genetic factors modifying the risk of both C9ALS and sporadic ALS (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Another downregulated miRNA-targeted gene, MYH15, has never been reported to be involved in antiphospholipid syndrome or other rheumatic diseases. Recent study has suggested the role of MYH15 in Amyotrophic lateral sclerosis (ALS), a fatal neurological disorder characterized by progressive muscular atrophy and respiratory failure [43]. The reduced expression of MYH15 in APS sample by qPCR was also not in concordant to its downregulated miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Another downregulated miRNA-targeted gene, MYH15, has never been reported to be involved in antiphospholipid syndrome or other rheumatic diseases. Recent study has suggested the role of MYH15 in Amyotrophic lateral sclerosis (ALS), a fatal neurological disorder characterized by progressive muscular atrophy and respiratory failure [43]. The reduced expression of MYH15 in APS sample by qPCR was also not in concordant to its downregulated miRNAs.…”
Section: Discussionmentioning
confidence: 99%